2010
DOI: 10.1002/jcp.22059
|View full text |Cite
|
Sign up to set email alerts
|

TLR4‐dependent induction of vascular adhesion molecule‐1 in rheumatoid arthritis synovial fibroblasts: Roles of cytosolic phospholipase A2α/cyclooxygenase‐2

Abstract: Lipopolysaccharide (LPS)/Toll-like receptor 4 (TLR4)-mediated signaling pathways have caught the attention of strategies designed for rheumatoid arthritis (RA). In this study, we identified that cPLA(2)alpha acted as a modulator of LPS-induced VCAM-1 expression and THP-1 (human acute monocytic leukemia cell line) adherence. Treatment of RA synovial fibroblasts (RASFs) with LPS, a TLR4 agonist, promoted the VCAM-1 expression and THP-1 adherence which were decreased by pretreatment with a selective cytosolic pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…In either case, the mechanisms are of obvious interest clinically even if some randomized controlled trials found little evidence showing that higher intake of omega 3 fatty acids affects the incidence of cancer [33]. It is likely that suppression of tumor cell growth by n-3 PUFAs is due to a combination (rather than one) of these mechanisms [32,[34][35][36][37]. It has been proposed that n-3 PUFAs included in the diet are incorporated into cell membranes of normal and tumor tissues where they serve as substrate for COX-2 and inhibit the expression of the inflammationproducing and growth-promoting prostaglandin E2 [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In either case, the mechanisms are of obvious interest clinically even if some randomized controlled trials found little evidence showing that higher intake of omega 3 fatty acids affects the incidence of cancer [33]. It is likely that suppression of tumor cell growth by n-3 PUFAs is due to a combination (rather than one) of these mechanisms [32,[34][35][36][37]. It has been proposed that n-3 PUFAs included in the diet are incorporated into cell membranes of normal and tumor tissues where they serve as substrate for COX-2 and inhibit the expression of the inflammationproducing and growth-promoting prostaglandin E2 [37].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that suppression of tumor cell growth by n-3 PUFAs is due to a combination (rather than one) of these mechanisms [32,[34][35][36][37]. It has been proposed that n-3 PUFAs included in the diet are incorporated into cell membranes of normal and tumor tissues where they serve as substrate for COX-2 and inhibit the expression of the inflammationproducing and growth-promoting prostaglandin E2 [37]. As cancer growth depends on development of new blood vessels to supply nutrients and to remove wastes, inhibition of angiogenesis may inhibit or limit tumor growth [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, LPS is commonly used as an activator of toll-like receptor 4 (TLR4), a pattern-recognition receptor that responds to pathogen-associated molecular patterns such as those present on invading bacteria. TLR4 is expressed on numerous cell types including immune cells (dendritic cell, monocyte and macrophage, B cells etc), epithelial cells, sensory neurons [1; 5; 8; 9; 12; 15] and has been shown in prior studies to be expressed on fibroblasts from other tissue origins such as those found in adventitia, lung, gingiva, and synovium [16; 17; 35; 37]. In addition to LPS, there are many endogenous ligands for TLR-4 such as the heat shock protein Gp96, fibrinogen, surfactant protein-A, high mobility group box 1 protein (HMGB1) and mRNA [31].…”
Section: Discussionmentioning
confidence: 99%
“…mRNA in RA > OA or non arthritic joints, at synovial lining, sites of attachment and invasion into cartilage or bone, around small vessels and in areas of infiltrating lymphocytes (fibroblasts not macrophages or T cells) yes (Seibl et al, 2003) Protein in RA > OA or healthy joints in synovial lining, sublining and perivascular regions nd Protein in RA blood monocytes, tissue macrophages yes (Iwahashi et al, 2004;Huang et al, 2007) Protein in fibroblasts from RA > OA joints > healthy skin yes TLR3 mRNA and protein in RA > OA or healthy synovium, in fibroblasts of the synovial lining and sublining, and in the perivascular areas yes (Brentano et al, 2005;Roelofs et al, 2005) Protein in fibroblasts from early RA > OA or healthy synovium yes (Ospelt et al, 2008) TLR4 mRNA in RA synovial tissue, protein in DCs and macrophages but not T cells or fibroblasts from RA joint yes ) (Tamaki et al, 2011) (Huang et al, 2007) Protein in synovial tissue from RA > OA > healthy joints, in early and longstanding RA yes ) (Ospelt et al, 2008) Protein in RA synovial fibroblasts yes Wu et al, 2010) TLR5 Protein in DCs> macrophages > fibroblasts from RA joint nd (Tamaki et al, 2011) TLR6 Protein in DCs> macrophages > fibroblasts from RA joint nd (Tamaki et al, 2011) TLR7 Protein in RA synovium > OA or healthy joints yes (Roelofs et al, 2005;Roelofs et al, 2009) TLR9 Protein in DCs> macrophages > fibroblasts from RA joint nd (Tamaki et al, 2011) nd = not determined F= function = the ability of the TLR to respond to its cognate ligand in each cell/tissue type Further studies using ex vivo human disease models have provided evidence of a functional role for TLRs in driving inflammation in RA. Adenoviral over expression of dominant negative Myd88, an adaptor molecule required for signalling by all TLRs except TLR3, inhibited cytokine synthesis in RA synovial cells .…”
Section: Tlrs and Ra Pathologymentioning
confidence: 99%